Composite polytetrafluoroethylene material and its preparation method and application

By combining modified PFA filler with polytetrafluoroethylene, the network structure of the modified composite filler makes PFA melted and polytetrafluoroethylene combine, solving the problem of insufficient wear resistance of polytetrafluoroethylene materials and improving its mechanics Performance and thermal conductivity, suitable for aerospace equipment.

CN119019794BActive Publication Date: 2025-01-07ANHUI ZHONGWANG KEXIMENG TECH CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411507143.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-10-28
Publication Date
2025-01-07
Estimated Expiration
2044-10-28

AI Technical Summary

Technical Problem

Polytetrafluoroethylene materials lack wear resistance in the aerospace field, and although the addition of fillers can improve, it will lead to a decrease in mechanical properties.

Method used

By mixing PFA and filler in a specific proportion, a modified PFA filler is formed and mixed with chain structure polymer compounds to form a modified composite filler, and then mix it with polytetrafluoroethylene and sintered, using the modified composite filler The network structure allows the melting of PFA and bonding with polytetrafluoroethylene to enhance the wear resistance and mechanical properties of the material.

Benefits of technology

The wear resistance and mechanical properties of polytetrafluoroethylene materials have been improved, ensuring their applicability in aerospace equipment, and significantly improving thermal conductivity and adhesion.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119019794B_ABST
    Figure CN119019794B_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of polytetrafluoroethylene materials, and discloses a composite polytetrafluoroethylene material, a preparation method thereof, and an application thereof. The preparation method of the composite polytetrafluoroethylene material comprises: mixing PFA and a filler in a mass ratio of 100:150-200, so that PFA is coated on the surface of the filler to obtain a modified PFA filler; uniformly mixing the modified PFA filler with a modified solution to obtain a mixed slurry, then volatilizing the solvent in the mixed slurry to obtain a modified composite filler having a network structure coating layer on the surface; uniformly mixing polytetrafluoroethylene and the modified composite filler in a mass ratio of 100:20-30 to obtain a mixture; and forming the mixture into a blank and then sintering. The finished rod material obtained by the preparation method has the characteristics of good wear resistance and good mechanical properties.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of polytetrafluoroethylene materials, and in particular to a composite polytetrafluoroethylene material and a preparation method and application thereof. Background Art

[0002] With the rapid development of the aerospace field, the field has higher requirements for mechanical properties and resistance to high and low temperature environments for sealing materials. Under this demand, polytetrafluoroethylene without any filler has the best tensile properties, elongation, and impact resistance, but polytetrafluoroethylene without any filler also has the disadvantage of low wear resistance. In order to solve the problem of polytetrafluoroethylene's non-wear resistance, fillers (such as carbon fiber, carbon black, graphite, copper powder and other wear-resistant materials) must be added, but adding fillers will cause some mechanical properties to be greatly reduced.

[0003] In view of this, the present invention is proposed. Summary of the invention

[0004] The object of the present invention is to provide a composite polytetrafluoroethylene material and a preparation method and application thereof, aiming to improve at least one problem mentioned in the background technology.

[0005] The present invention is achieved in that:

[0006] In a first aspect, the present invention provides a method for preparing a composite polytetrafluoroethylene material, comprising:

[0007] Mixing PFA and filler in a mass ratio of 100:150-200, so that PFA is coated on the surface of the filler to obtain a modified PFA filler;

[0008] The modified PFA filler and the modified solution are uniformly mixed to obtain a mixed slurry, and then the solvent in the mixed slurry is volatilized to obtain a modified composite filler with a network structure coating layer on the surface, the solute in the modified solution is a chain structure polymer compound, the mass ratio of the modified PFA filler to the chain structure polymer compound is 100:40-90, and the chain structure polymer compound is selected from at least one of polyimide, polyetheretherketone and polyethersulfone;

[0009] The polytetrafluoroethylene and the modified composite filler are mixed in a mass ratio of 100:20-30 to obtain a mixture;

[0010] forming the mixed material into a blank;

[0011] The blank is sintered to make the PFA coated on the surface of the modified composite filler melt out and pass through the gaps of the network structure coating layer, and the melted PFA is combined with polytetrafluoroethylene, and then the temperature is lowered to obtain a finished rod;

[0012] The filler is selected from at least one of carbon fiber, copper powder, molybdenum disulfide and glass fiber.

[0013] In an optional embodiment, the solvent in the modified solution is selected from at least one of dimethyl sulfoxide, N,N-dimethylformamide, N-methylpyrrolidone, trichloroacetic acid and dimethylacetamide.

[0014] In an optional embodiment, at least one of the following features (1) and (2) is included:

[0015] (1) The mass concentration of the solute in the modified solution is 10~15%;

[0016] (2) Methods for volatilizing the solvent in the mixed slurry include:

[0017] The mixed slurry is placed in a spray gun at 70 to 200 times the atmospheric pressure using a high-pressure pump to polymerize the mixed slurry into mist particles of 10 to 200 μm, and then is exposed to heat exchange with hot air at a temperature of 350 to 370°C, and the solvent evaporates to obtain a modified composite filler.

[0018] In an optional embodiment, at least one of the following features (1) to (3) is included:

[0019] (1) The method of mixing PFA with filler and coating the surface of the filler with PFA to obtain modified PFA filler includes:

[0020] Mixing PFA and filler at a rotation speed of 1000-1500 r / min for 10-15 min to obtain a primary modified material;

[0021] The primary modified material is spread on the bubbling fluidized bed with a thickness of ≤0.5mm, and the air inlet temperature of the bubbling fluidized bed is set to 50℃~100℃, the temperature in the second section of the pipeline is controlled to 340℃~380℃, the temperature in the third section of the pipeline is controlled to 350℃~380℃, and the temperature of the cold air introduced before discharging is 15~30℃;

[0022] The modified PFA filler was obtained after being treated in a bubbling fluidized bed;

[0023] (2) The method of mixing the polytetrafluoroethylene and the modified composite filler includes: mixing the modified composite filler and the polytetrafluoroethylene at a rotation speed of 1200-1500 r / min for 3-10 minutes;

[0024] (3) The method of molding the mixture into a blank is as follows: the mixture is molded at a pressure of 38-40 MPa and a holding time of 6-12 minutes.

[0025] In an optional embodiment, the particle size of the filler is 10-25 μm, and the particle size of the modified PFA filler is 25-35 μm.

[0026] In an optional embodiment, the sintering conditions for sintering the blank include: keeping the blank at 370-390° C. for 5-10 hours.

[0027] In an optional embodiment, the sintering conditions for sintering the blank are:

[0028] Place the blank in a heating device, increase the temperature of the heating device to 190~210℃ at a heating rate of 55~65℃ / h; then increase the temperature of the heating device to 310~330℃ at a heating rate of 35~45℃ / h, and keep it warm for 1~2h; then increase the temperature of the heating device to 370~390℃ at a heating rate of 20~25℃ / h, and keep it warm for 5~10h; then cool it down to 310~330℃ at a cooling rate of 20~25℃ / h, and keep it warm for 1~2h; then cool it down to 190~210℃ at 40~45℃ / h, and then cool it down freely.

[0029] In a second aspect, the present invention provides a finished bar material, which is prepared by the preparation method of any one of the aforementioned embodiments.

[0030] In a third aspect, the present invention provides the use of the composite polytetrafluoroethylene material according to the aforementioned embodiment in equipment in the aerospace field.

[0031] The present invention has the following beneficial effects:

[0032] PEEK and PES have good compatibility with PFA. The polarity of these two substances makes their adhesion to fillers much greater than that of PFA. PI has good compatibility with PFA. It has electron adsorption with fillers, and its adhesion to fillers is also much greater than that of PFA. The modified PFA is coated on the surface of the filler. Due to the presence of PEEK, PES or PI, the modified PFA has a strong bonding force with the filler. The modified composite filler is mixed with polytetrafluoroethylene and then sintered. During the sintering process, the PFA coated on the surface of the modified composite filler partially melts through the gaps in the network structure coating layer. The melted PFA molecular chain unfolds and forms a molecular entanglement with polytetrafluoroethylene. The two are stably combined, thereby achieving a stable combination of the filler and polytetrafluoroethylene. In the present invention, due to the special coating treatment of the filler, the filler is composited with polytetrafluoroethylene and then sintered, the filler has better thermal conductivity, and the heating uniformity is improved compared with the polytetrafluoroethylene without filler during the heating process. Therefore, when the ratio of the modified composite filler to polytetrafluoroethylene is within the range required by the present invention, the prepared composite polytetrafluoroethylene material not only has good wear resistance, but also has the characteristics of mechanical properties that are not inferior to or even better than those of the polytetrafluoroethylene material without filler.

[0033] Therefore, the composite polytetrafluoroethylene material prepared by the method for preparing the composite polytetrafluoroethylene material provided by the present invention has better wear resistance and mechanical properties, and the material can be used as a sealing material in aerospace equipment. BRIEF DESCRIPTION OF THE DRAWINGS

[0034] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for use in the embodiments are briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present invention and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without creative work.

[0035] Figure 1 The SEM image of the PEEK network structure coated with modified PFA filler;

[0036] Figure 2 The SEM image of the PES network structure coated with PFA filler;

[0037] Figure 3 This is a SEM image of the fractured section of the finished product obtained in Example 2;

[0038] Figure 4 This is a SEM image of the fractured cross section of the finished product obtained in Example 3;

[0039] Figure 5 This is the SEM image of the fractured cross section of the finished product obtained in Comparative Example 2. DETAILED DESCRIPTION

[0040] In order to make the purpose, technical scheme and advantages of the embodiments of the present invention clearer, the technical scheme in the embodiments of the present invention will be described clearly and completely below. If the specific conditions are not specified in the embodiments, they are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be purchased commercially.

[0041] The composite polytetrafluoroethylene material provided in the embodiments of the present invention and its preparation method and application are described in detail below.

[0042] The Chinese names corresponding to the English abbreviations in this article are as follows:

[0043] PFA: fluoroethylene-perfluoroalkoxy vinyl ether copolymer;

[0044] PEEK: polyetheretherketone;

[0045] PES: polyethersulfone;

[0046] PI: Polyimide.

[0047] The preparation method of the composite polytetrafluoroethylene material provided in the embodiment of the present invention is specifically as follows:

[0048] S1. Preparation of modified PFA filler

[0049] Mixing PFA and the filler at a mass ratio of 100:150-200 at a rotation speed of 1000-1500 r / min for 10-15 minutes to obtain a primary modified material;

[0050] The primary modified material is spread on the bubbling fluidized bed with a thickness of ≤0.5 mm, the air inlet temperature of the bubbling fluidized bed is set to 50°C-100°C, the temperature in the second section of the pipeline is controlled to 340°C-380°C, the temperature in the third section of the pipeline is controlled to 350°C-380°C, and the temperature of the cold air introduced before discharging is 15-30°C;

[0051] The modified PFA filler is obtained after the bubbling fluidized bed treatment.

[0052] Optionally, the particle size of the filler is 10-25 μm;

[0053] Optionally, the particle size of the modified PFA filler is 25-35 μm.

[0054] Optionally, the filler is selected from at least one of carbon fiber, copper powder, molybdenum disulfide and glass fiber. These fillers are currently the types of fillers with better wear resistance for enhancing polytetrafluoroethylene.

[0055] S2. Preparation of modified composite filler

[0056] First, the solute and the solvent are evenly mixed to obtain a modified solution with a solute mass concentration of 10-15%. Optionally, the solute in the modified solution is selected from at least one of PEEK (polyetheretherketone), PES (polyethersulfone) and PI (polyimide).

[0057] PEEK, PES and PI are in a melted state in the solution, and the degree of polymerization is between 80,000 and 290,000.

[0058] Optionally, the solvent in the modified solution is selected from at least one of dimethyl sulfoxide, N,N-dimethylformamide, N-methylpyrrolidone, trichloroacetic acid and dimethylacetamide.

[0059] Then, the modified PFA filler and the modified solution are mixed to obtain a mixed slurry, and the solvent in the mixed slurry is volatilized to obtain the modified PFA.

[0060] Optionally, in order to make the prepared material have better wear resistance and mechanical properties, in this step, the modified PFA filler and the chain structure polymer compound are mixed in a mass ratio of 100:40-90.

[0061] Furthermore, in order to make the modified PFA filler more uniformly dispersed in the modified solution, the modified PFA filler and the modified solution are mixed to obtain a mixed slurry in the following manner:

[0062] First, the modified PFA filler particles and ethyl acetate are mixed and dispersed evenly in a mass ratio of 1:1 to obtain a dispersion; then the dispersion is mixed with the modified solution in a mass ratio of 200:400~600.

[0063] Optionally, the method of volatilizing the solvent in the mixed slurry includes:

[0064] The method of volatilizing the solvent in the mixed slurry is, for example, to use a high-pressure pump to pass the mixed slurry through an atomizer (spray gun) at a pressure of 70 to 200 times the atmospheric pressure, and polymerize it into mist particles of 10 to 200 microns, which are directly in contact with hot air at a temperature of 350 to 370°C for heat exchange, and dry it in 1 to 3 minutes to obtain a modified composite filler.

[0065] S3, Hybrid Molding

[0066] The polytetrafluoroethylene and the modified composite filler are mixed at a mass ratio of 100:20-30 at a rotation speed of 1000-1500 r / min for 3-10 minutes to obtain a mixture;

[0067] The mixed material is molded at a molding pressure of 38-40 MPa and a holding time of 6-12 min to obtain a blank.

[0068] S4, Sintering

[0069] The blank is sintered to make the PFA coated on the surface of the modified composite filler particles melt out and pass through the gaps of the network structure coating layer, and the melted PFA is combined with the polytetrafluoroethylene, and then the temperature is reduced to obtain a finished rod.

[0070] Optionally, to achieve the above-mentioned melting of PFA through the gaps in the network structure coating layer, the sintering conditions for combining the melted PFA with polytetrafluoroethylene include placing the blank at 370-390° C. for 5-10 hours.

[0071] Specifically, the sintering conditions are:

[0072] Place the blank in a heating device, increase the temperature of the heating device to 190~210℃ at a heating rate of 55~65℃ / h; then increase the temperature of the heating device to 310~330℃ at a heating rate of 35~45℃ / h, and keep it warm for 1~2h; then increase the temperature of the heating device to 370~390℃ at a heating rate of 20~25℃ / h, and keep it warm for 5~10h; then cool it down to 310~330℃ at a cooling rate of 20~25℃ / h, and keep it warm for 1~2h; then cool it down to 190~210℃ at 40~45℃ / h, and then cool it freely to obtain the finished bar.

[0073] Since PTFE conducts heat slowly, using step-by-step heating and cooling can avoid the problem of product cracking caused by a large temperature difference between the inside and outside due to too fast a heating rate. Therefore, step-by-step heating and cooling can ensure that a material with better performance is produced.

[0074] The above preparation method can form a preliminary material with a desired structure through different molds, and can directly obtain the desired object after sintering; or the sintered material can be cut to obtain the final desired object.

[0075] The composite polytetrafluoroethylene material provided in the embodiment of the present invention is prepared by the preparation method provided in the embodiment of the present invention.

[0076] The composite polytetrafluoroethylene material provided in the embodiment of the present invention can be used in equipment in the aerospace field because of its good mechanical properties and wear resistance.

[0077] The features and performances of the present invention are further described in detail below in conjunction with the embodiments.

[0078] Example 1

[0079] PFA and filler (carbon fiber) with a particle size of 10-25 μm were mixed at a mass ratio of 100:150 at a rotation speed of 1000 r / min for 15 minutes to obtain a primary modified material;

[0080] The primary modified material is spread on a bubbling fluidized bed with a thickness of 0.3 mm, the air inlet temperature of the fluidized bed is set to 50° C., the temperature in the second-stage pipeline is controlled to 340° C., the temperature in the third-stage pipeline is controlled to 350° C., and the temperature of the cold air introduced before discharging is 15° C. to obtain a modified PFA filler, and the particle size of the modified PFA filler is 25-35 μm.

[0081] PI was mixed with dimethyl sulfoxide to obtain a modified solution with a PI concentration of 10%;

[0082] The modified PFA filler and ethyl acetate are mixed and dispersed evenly in a mass ratio of 1:1 to obtain a dispersion;

[0083] The dispersed material and the modified solution were mixed in a mass ratio of 200:400.

[0084] Using a high-pressure pump, the mixed slurry is passed through an atomizer (spray gun) at a pressure of 70 times the atmospheric pressure, and is polymerized into mist particles of 10 to 200 microns, which are directly in contact with hot air at a temperature of 350°C for heat exchange. The modified composite filler is dried in 3 minutes.

[0085] The polytetrafluoroethylene and the modified composite filler were mixed at a mass ratio of 100:25 at a rotation speed of 1000 r / min for 10 minutes to obtain a mixture;

[0086] The mixed material is molded at a molding pressure of 38 MPa and a holding time of 12 min to obtain a blank.

[0087] Place the blank in a heating device, and increase the temperature of the heating device to 200°C at a heating rate of 60°C / h; then increase the temperature of the heating device to 320°C at a heating rate of 40°C / h, and keep it warm for 1.5 hours; then increase the temperature of the heating device to 380°C at a heating rate of 22°C / h, and keep it warm for 7 hours; then cool it down to 320°C at a cooling rate of 22°C / h, and keep it warm for 1.5 hours; then cool it down to 200°C at 42°C / h, and then cool it freely to obtain the finished bar.

[0088] Example 2

[0089] PFA and filler (copper powder) with a particle size of 10-25 μm were mixed at a mass ratio of 100:200 at a speed of 1500 r / min for 10 min to obtain a primary modified material;

[0090] The primary modified material was spread on a bubbling fluidized bed with a thickness of 0.4 mm, the air inlet temperature of the fluidized bed was set to 100° C., the temperature in the second-stage pipeline was controlled to 380° C., the temperature in the third-stage pipeline was controlled to 100° C., and the temperature of the cold air introduced before discharging was 30° C. to obtain a modified PFA filler, the particle size of the modified PFA filler was 25-35 μm.

[0091] PEEK was mixed with N-methylpyrrolidone to obtain a modified solution having a PEEK concentration of 15%;

[0092] The modified PFA filler and ethyl acetate are mixed and dispersed evenly in a mass ratio of 1:1 to obtain a dispersion;

[0093] The dispersed material and the modified solution were mixed in a mass ratio of 200:600.

[0094] Using a high-pressure pump, the mixed slurry is passed through an atomizer (spray gun) at a pressure of 200 times the atmospheric pressure, and is polymerized into mist particles of 10 to 200 microns, which are directly in contact with hot air at a temperature of 370°C for heat exchange. The modified composite filler is dried in 1 minute.

[0095] The polytetrafluoroethylene and the modified composite filler were mixed at a mass ratio of 100:25 at a rotation speed of 1500 r / min for 3 minutes to obtain a mixture;

[0096] The mixed material is molded at a molding pressure of 40 MPa and a holding time of 6 min to obtain a blank.

[0097] The blank was placed in a heating device, and the temperature of the heating device was increased to 210°C at a heating rate of 55°C / h; then the temperature of the heating device was increased to 330°C at a heating rate of 35°C / h, and kept warm for 1h; then the temperature of the heating device was increased to 370°C at a heating rate of 25°C / h, and kept warm for 10h; then the temperature was decreased to 310°C at a cooling rate of 20°C / h, and kept warm for 1h; then the temperature was decreased to 210°C at a cooling rate of 40°C / h, and then the finished bar was obtained by free cooling.

[0098] Example 3

[0099] PFA and a filler (molybdenum disulfide) with a particle size of 10-25 μm were mixed at a mass ratio of 100:180 at a rotation speed of 1300 r / min for 12 minutes to obtain a primary modified material;

[0100] The primary modified material is spread on a bubbling fluidized bed with a thickness of 0.5 mm, the air inlet temperature of the fluidized bed is set to 80° C., the temperature in the second-stage pipeline is controlled to 360° C., the temperature in the third-stage pipeline is controlled to 100° C., and the temperature of the cold air introduced before discharging is 30° C. to obtain a modified PFA filler, and the particle size of the modified PFA filler is 25~35 μm.

[0101] Mixing PES with N,N-dimethylformamide to obtain a modified solution having a PES concentration of 13%;

[0102] The modified PFA filler and ethyl acetate are mixed and dispersed evenly in a mass ratio of 1:1 to obtain a dispersion;

[0103] The dispersed material and modified solution were mixed in a mass ratio of 200:500.

[0104] Using a high-pressure pump, the mixed slurry is passed through an atomizer (spray gun) at a pressure of 150 times the atmospheric pressure, and is polymerized into mist particles of 10 to 200 microns, which are directly in contact with hot air at a temperature of 360°C for heat exchange. The modified composite filler is dried in 2 minutes.

[0105] Polytetrafluoroethylene and modified composite filler were mixed at a mass ratio of 100:25 at a rotation speed of 1500 r / min for 3 minutes to obtain a mixture.

[0106] The mixed material is molded at a molding pressure of 38 MPa and a holding time of 6 min to obtain a blank;

[0107] The blank was placed in a heating device, and the temperature of the heating device was increased to 190°C at a heating rate of 65°C / h; then the temperature of the heating device was increased to 310°C at a heating rate of 45°C / h, and kept warm for 2h; then the temperature of the heating device was increased to 390°C at a heating rate of 20°C / h, and kept warm for 5h; then the temperature was decreased to 330°C at a cooling rate of 25°C / h, and kept warm for 2h; then the temperature was decreased to 190°C at a cooling rate of 45°C / h, and then the finished bar was obtained by free cooling.

[0108] Example 4

[0109] This embodiment is basically the same as the embodiment 1, except that the mass ratio of polytetrafluoroethylene to the modified composite filler is 100:20.

[0110] Example 5

[0111] This embodiment is basically the same as the embodiment 1, except that the mass ratio of polytetrafluoroethylene to the modified composite filler is 100:30.

[0112] Comparative Example 1

[0113] This embodiment is basically the same as Embodiment 1, except that:

[0114] Without adding modified composite filler, polytetrafluoroethylene is directly molded and then sintered. The molding and sintering parameters are the same as those in Example 1.

[0115] Comparative Example 2

[0116] No modification is done on the carbon fiber. The solution is:

[0117] Unmodified carbon fiber and polytetrafluoroethylene were mixed at a mass ratio of 25:100 at a rotation speed of 1000 r / min for 10 min to obtain a mixture;

[0118] The mixed material is molded and then sintered.

[0119] The carbon fiber used in this embodiment is the same as that used in Example 1, and the operating parameters of molding and sintering are the same as those in Example 1.

[0120] Comparative Example 3

[0121] The copper powder is not modified. The solution is:

[0122] Unmodified copper powder and polytetrafluoroethylene were mixed at a mass ratio of 25:100 at a rotation speed of 1500 r / min for 3 min to obtain a mixture;

[0123] The mixed material is molded and then sintered.

[0124] The copper powder used in this embodiment is the same as that used in Embodiment 2, and the operation parameters of molding and sintering are the same as those in Embodiment 2.

[0125] Comparative Example 4

[0126] This embodiment is basically the same as the embodiment 1, except that after obtaining the modified PFA filler, it is not compounded with PI but directly mixed with polytetrafluoroethylene and pressed to obtain the finished rod.

[0127] Comparative Example 5

[0128] This comparative example is substantially the same as Example 5, except that the mass ratio of the modified composite filler to polytetrafluoroethylene is 40:100.

[0129] Comparative Example 6

[0130] This comparative example is basically the same as Example 2, except that the dispersion material and the modified solution are mixed in a mass ratio of 200:800, that is, the ratio of the modified PFA filler to PEEK is 100:120.

[0131] Comparative Example 7

[0132] This comparative example is basically the same as Example 2, except that PFA and a filler (copper powder) with a particle size of 10-25 μm are mixed at a mass ratio of 150:150 at a rotation speed of 1000 r / min for 15 minutes to obtain a primary modified material.

[0133] Comparative Example 8

[0134] This comparative example is basically the same as Example 1, except that no sintering is performed after the blank is made.

[0135] The result is: the blank cannot be processed into a specimen, cannot be formed, and cannot be tested.

[0136] Experimental Example 1

[0137] The wear resistance and mechanical properties of the finished rods prepared in various embodiments and comparative examples were tested.

[0138] The mechanical properties were tested according to GB / T1040, and the wear scar width was measured at 23°C for 120 min according to GB / T3960. The test results are recorded in Table 1.

[0139] Table 1 Wear resistance and mechanical properties test results of various embodiments and comparative examples

[0140]

[0141] Note: “ / ” in Table 1 means no data. When the wear resistance test of Example 1 was carried out, the material was worn through in the 5th minute, and the data collection was invalid.

[0142] It can be seen from Table 1 that the finished rods prepared in various embodiments of the present invention have excellent wear resistance and mechanical properties.

[0143] The wear resistance of each embodiment is significantly better than that of comparative example 1, indicating that the preparation method provided by the present invention can improve the wear resistance of polytetrafluoroethylene. Compared with the mechanical properties, the mechanical properties of multiple embodiments provided by the present invention are not worse than or even better than those of comparative example 1, indicating that the composite polytetrafluoroethylene material prepared by the preparation method provided by the present invention has good mechanical properties.

[0144] The mechanical properties of Examples 1 and 2 are better than those of Comparative Examples 2 and 3, respectively, indicating that the preparation method provided by the present invention can significantly improve the mechanical properties of the composite material compared to directly adding fillers to polytetrafluoroethylene; and the wear resistance of the embodiments is also better than that of the comparative examples, which indicates that the preparation method provided by the present invention can also increase the wear resistance of the composite filler by modifying the filler.

[0145] Comparing Example 1 with Comparative Example 4, the mechanical properties of Comparative Example 4 are significantly lower, indicating that if only PFA-coated fillers are used without network structure-coated fillers, it is difficult to achieve ideal mechanical properties.

[0146] Comparing Example 5 with Comparative Example 5, the wear resistance and mechanical properties of Comparative Example 5 are significantly worse, indicating that excessive addition of filler will reduce the mechanical properties too much, which will affect its use.

[0147] Comparing Example 2 with Comparative Example 6, the wear resistance of Comparative Example 6 is significantly worse, indicating that the amount of PEEK-coated modified PFA filler should not be too much, as too much will reduce the wear resistance.

[0148] Comparing Example 2 with Comparative Example 7, the wear resistance of Comparative Example 7 is significantly worse, indicating that the amount of PFA coated filler should not be too much, as too much will reduce the wear resistance.

[0149] Experimental Example 2

[0150] The microstructure of the modified composite filler obtained during the preparation of Example 2 and Example 3 is shown in FIG. Figures 1 to 3 As shown;

[0151] Figure 1This is a SEM image of the PEEK network structure coated with the modified PFA filler. It can be seen from the figure that the surface of the modified PFA filler is coated with the PEEK network structure. Figure 2 This is the SEM image of the modified PFA filler coated with the PES network structure. It can be seen from the figure that the surface of the modified PFA filler is coated with the PES network structure.

[0152] SEM images of the fractured cross-sections of the finished products obtained in Examples 2 and 3 are taken, respectively. Figure 3 and Figure 4 As shown, from Figure 3 and Figure 4 It can be seen from the figure that the cross section of the finished rod material is rough, which indicates that the bonding force between the resin particles and the filler is excellent; the SEM image of the cross section of the finished product after fracture obtained in Comparative Example 2 is taken, as shown in FIG. Figure 5 As shown, from Figure 5 It can be seen that the cross section is smooth, that is, the adhesion between polytetrafluoroethylene and the filler is poor.

[0153] In summary, the preparation method of the composite polytetrafluoroethylene material provided by the present invention utilizes PFA particles to modify the filler to obtain a modified PFA filler, and then the modified PFA filler is modified with PEEK / PES / PI, and then combined with polytetrafluoroethylene. The prepared finished rod material has better wear resistance and mechanical properties. The material can be used as a sealing material in aerospace equipment.

[0154] The above are only preferred embodiments of the present invention and are not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A method for preparing a composite polytetrafluoroethylene material, characterized in that: include: Mixing PFA and filler in a mass ratio of 100:150-200, so that PFA is coated on the surface of the filler to obtain a modified PFA filler; The modified PFA filler and the modified solution are uniformly mixed to obtain a mixed slurry, and then the solvent in the mixed slurry is volatilized to obtain a modified composite filler with a network structure coating layer on the surface, wherein the solute in the modified solution is a chain structure polymer compound, the mass ratio of the modified PFA filler to the chain structure polymer compound is 100:40-90, and the chain structure polymer compound is selected from at least one of polyimide, polyetheretherketone and polyethersulfone; The polytetrafluoroethylene and the modified composite filler are mixed in a mass ratio of 100:20-30 to obtain a mixture; forming the mixed material into a blank; The blank is sintered to allow the PFA coated on the surface of the modified composite filler to melt out and pass through the gaps of the network structure coating layer, and the melted PFA is combined with the polytetrafluoroethylene, and then the temperature is reduced to obtain a finished rod; The filler is selected from at least one of carbon fiber, copper powder and molybdenum disulfide.

2. The preparation method according to claim 1, characterized in that: The solvent in the modified solution is selected from at least one of dimethyl sulfoxide, N,N-dimethylformamide, N-methylpyrrolidone, trichloroacetic acid and dimethylacetamide.

3. The preparation method according to claim 1, characterized in that: The invention comprises at least one of the following features (1) and (2): (1) The mass concentration of the solute in the modified solution is 10-15%; (2) The method of volatilizing the solvent in the mixed slurry includes: The mixed slurry is placed in a spray gun at 70 to 200 times atmospheric pressure using a high-pressure pump to polymerize the mixed slurry into mist particles of 10 to 200 μm, and then is exposed to heat exchange with hot air at a temperature of 350 to 370° C. to evaporate the solvent to obtain the modified composite filler.

4. The preparation method according to claim 1, characterized in that: Includes at least one of the following features (1) to (3): (1) The method of mixing PFA with the filler so that PFA is coated on the surface of the filler to obtain a modified PFA filler includes: Mixing PFA and the filler at a rotation speed of 1000-1500 r / min for 10-15 min to obtain a primary modified material; The primary modified material is spread on the bubbling fluidized bed with a thickness of ≤0.5 mm, the air inlet temperature of the bubbling fluidized bed is set to 50°C-100°C, the temperature in the second section of the pipeline is controlled to 340°C-380°C, the temperature in the third section of the pipeline is controlled to 350°C-380°C, and the temperature of the cold air introduced before discharging is 15-30°C; The modified PFA filler is obtained after the bubbling fluidized bed treatment; (2) The method of mixing the polytetrafluoroethylene and the modified composite filler comprises: mixing the modified composite filler and the polytetrafluoroethylene at a rotation speed of 1200-1500 r / min for 3-10 minutes; (3) The method of molding the mixed material into a blank is as follows: molding the mixed material at a pressure of 38-40 MPa and holding the pressure for 6-12 minutes.

5. The preparation method according to claim 1, characterized in that: The particle size of the filler is 10-25 μm, and the particle size of the modified PFA filler is 25-35 μm.

6. The preparation method according to claim 1, characterized in that: The sintering conditions for sintering the blank include: placing the blank at 370-390° C. and keeping it warm for 5-10 hours.

7. The preparation method according to claim 6, characterized in that: The sintering conditions for sintering the blank are: The blank is placed in a heating device, and the temperature of the heating device is increased to 190-210°C at a heating rate of 55-65°C / h; then the temperature of the heating device is increased to 310-330°C at a heating rate of 35-45°C / h, and kept warm for 1-2h; then the temperature of the heating device is increased to 370-390°C at a heating rate of 20-25°C / h, and kept warm for 5-10h; then the temperature is reduced to 310-330°C at a cooling rate of 20-25°C / h, and kept warm for 1-2h; then the temperature is reduced to 190-210°C at a cooling rate of 40-45°C / h, and then the temperature is reduced freely.

8. A composite polytetrafluoroethylene material, characterized in that: The method is prepared according to any one of claims 1 to 7.

9. Use of the composite polytetrafluoroethylene material as claimed in claim 8 in equipment in the aerospace field.

Citation Information

Patent Citations

  • Modified PTFE (polytetrafluoroethylene) hose and preparation method thereof

    CN109320885A

  • Processing method of modified polytetrafluoroethylene sealing element

    CN115091774A